BIZARRE THYROID FUNCTION TEST IN A PATIENT WITH MULTINODULAR GOITRE: A CASE REPORT - Tan, Jie En; Tan, Florence Hui Sieng; Kuan, Yueh Chien; Chan, Pei Lin (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Multinodular goitres may be accompanied by various thyroid function abnormalities. Assessment of thyroid status and correct interpretation of thyroid function tests (TFTs) is important to ascertain the aetiology. CASE A 68-year-old female was referred for re-evaluation of abnormal TFT associated with a huge multinodular goitre. She was seen 3 years ago by a private practitioner due to progressive goitre enlargement since age 30 years. TFTs then showed markedly reduced fT4 at 1.3-3.6 pmol/L (12-22), with normal TSH at 0.3-0.65 µIU/mL (0.27-4.2). She was started on L-thyroxine 100 ug daily based on these results, but she was only taking it intermittently. At the time of evaluation, there was no sign or symptom of hypothyroidism, but she complained of weight loss and irritability. On examination, she had a huge goitre with no lymphadenopathy. TFTs done showed low fT4, 8.6 pmol/L and TSH <0.005 µIU/mL. Central hypothyroidism was ruled out by a paucity of signs of hypothyroidism with no accompanying hypopituitarism. Due to the persistent and markedly suppressed TSH (<0.005) but fT4 at a low normal limit, fT3 was assessed and was found to be elevated at 11-16.7 pmol/L (3.1-6.8). L-thyroxine was stopped. Three months later, a repeat TFT off L-thyroxine still showed a very low fT4 at 1.94 pmol/L, but normal fT3 (5.02 nmol/L) and TSH (0.291 µIU/mL). SHBG was normal at 52.4 nmol/L (16.8- 125.2) supporting euthyroidism. She remained well and euthyroid on subsequent follow-up with similar TFT but refused FNAC or surgical intervention for her goitre. CONCLUSION Low fT4 with normal TSH points towards central hypothyroidism but in patients with goitre and clinically euthyroid, disorders like iodine deficiency and thyroid dyshormonogenesis need to be considered. A T3 measurement should be done. A high T3/T4 ratio may be found in rarer entities such as resistance to thyroid hormone α and has also been reported in follicular thyroid cancer due to increased thyroidal deiodinase activity.